Countering Tobacco Industry Interference: A Policy Brief on Strengthening the WHO FCTC Article 5.3 Adoption in India - Sonu Goel; Priyobrat Rajkhowa; Shivam Kapoor; Ashish K. Pandey; Rana J Singh (Indian Journal of Community Medicine)
Tobacco use in India contributes to over 1.35 million deaths annually, posing a major public health challenge. Tobacco industry interference (TII) is a significant barrier to effective tobacco control, especially in low- and middle-income countries (LMICs), such as India. This interference undermines public health efforts by manipulating policy implementation and enforcement. The adoption of the World Health Organization Framework Convention on Tobacco Control (WHO FCTC) Article 5.3 in India has made progress, with 23 states implementing the guidelines. However, enforcement gaps and persistent tobacco industry (TI) tactics continue to weaken tobacco control measures. Nefarious strategies, such as lobbying and misinformation, further complicate the effective execution of these policies. To effectively reduce tobacco use in India, stronger and enforceable policies are needed at both national and state levels. Strengthened legal frameworks, increased public awareness, and robust monitoring systems are critical to protect public health policies from TII. These steps are essential to safeguard public health and enhance the impact of tobacco control initiatives.